Effectiveness Of The Detection Algorithm For The Comparison Of Negative Content On The Consumption Patterns Of Generation Z In The Social Media Application Tiktok - Fatih Afif Nasution; Alfin Faiz Pratama; sahril reza robert; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
TikTok, a short video-sharing app launched by ByteDance in 2016, has become a global phenomenon with millions of daily active users worldwide. This research explores TikTok's social dynamics and impact on various aspects of its users' lives. The main focus of the study is on how the app facilitates creativity, social interaction, and the formation of digital identities, particularly among Generation Z. Data was collected through survey methods, in-depth interviews, and content analysis from popular TikTok videos. The findings of the study show that TikTok has succeeded in creating an inclusive and dynamic platform, where users can express themselves freely through various video formats. However, there are also concerns related to privacy, data security, and the psychological impact of excessive content consumption.